2019
DOI: 10.1186/s12913-019-4456-8
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ perceptions of patient safety culture in Norwegian nursing homes and home care services

Abstract: Background Most health care services are provided in the primary health care sector, and an increasing number of elderly is in need of these services. Nonetheless, the research on patient safety culture in home care services and nursing homes remains scarce. This study describes staff perceptions of patient safety culture in Norwegian home care services and nursing homes, and assesses how various patient safety culture dimensions contribute to explaining overall perceptions of patient safety. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
71
5
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 34 publications
8
71
5
7
Order By: Relevance
“…A recent Norwegian study found that communication, openness and staffing were significant predictors of staff's overall perception of patient safety in nursing homes, yet the nursing home staff scored low on these dimensions [56]. This finding aligns with our study, which revealed that care managers find it difficult to distinguish between prioritising and patient neglect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A recent Norwegian study found that communication, openness and staffing were significant predictors of staff's overall perception of patient safety in nursing homes, yet the nursing home staff scored low on these dimensions [56]. This finding aligns with our study, which revealed that care managers find it difficult to distinguish between prioritising and patient neglect.…”
Section: Discussionsupporting
confidence: 90%
“…Leaders' abilities to promote a safety culture for both the resident and staff are linked to their leadership skills, knowledge of the resident's needs and their capacity to implement effective safety care practices [6,31,32]. Care managers' lack of awareness in identifying and following up on abuse will necessarily affect the safety culture in the organisation and, in the end, clinical outcomes such as quality and safe care for the residents [6,10,56].…”
Section: Discussionmentioning
confidence: 99%
“…and 'compliance with procedures' dimensions are the priority areas to be improved in nursing homes, as they had the lowest scores and the lowest PRRs. A similar situation was found in other countries, such as the USA (Smith et al, 2018), Belgium (Desmedt et al, 2018) and Norway (Ree & Wiig, 2019). The majority of staff are reported to be under-educated, lack experience and are only temporarily employed, which was confirmed in a similar study (Yang et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…An effective reporting system identi es safe behaviors that should be adapted to prevent errors, encompassing the individuals' adherence to their safety responsibilities, promises to maintain patient safety, efforts to acquire the latest knowledge on patient safety, and their learnings based on errors to achieve safety goals [47]. Further, noting the nding that administering a patient safety education program to nursing home staff led to a reduction of potential safety incidents (e.g., falls and pressure ulcers) by increasing the staff's awareness of PSC [48], establishing a standardized educational system for nursing home staff is crucial. Thus, teamwork and personnel management founded on open communication, trust, and cooperation within the organization are warranted [49].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, nurses play an important role in identifying and managing risk to ensure patient safety at nursing homes [30,31]. The main patient safety activities in LTC facilities include prevention of falls, pressure ulcers, infection, medication safety, inspection of equipment, re safety, and education for residents [32,33]. Previous studies have investigated employees' perceptions of PSC in nursing homes [4,5,[34][35][36][37], but research on the relationship between the perceptions of PSC and patient safety activities of nursing staff is inadequate.…”
mentioning
confidence: 99%